Clinical and pathological features of patients with antineutrophil cytoplasmic antibody‐associated vasculitides concomitant with IgG4‐related disease. (20th October 2019) - Ma, Yanhong; Chen, Liangliang; Xu, Ying; Han, Quan; Yu, Binfeng; Yuan, Yuan; Zhao, Jie; Yang, Yi; Chen, Jianghua; Han, Fei
Abstract: Aim: The characteristics and the pathogenesis of the concomitant antineutrophil cytoplasmic antibody (ANCA)‐associated vasculitides (AAV) and immunoglobulin G4‐related disease (IgG4‐RD) have not been elucidated. Method: We included 92 AAV patients with renal biopsy results. Among them, 10 patients met both AAV and IgG4‐RD criteria (concomitant group). The IgG subclasses of myeloperoxidase (MPO)‐ANCA in both serum and renal tissue were measured and complement activation components were detected in serum. Results: Patients in the concomitant group had both elevated serum IgG4 levels and positive MPO‐ANCA. They had higher levels of eosinophil counts, serum globulin, IgG, IgE and C‐reactive protein than patients in the AAV alone group. All 10 patients had glomerulonephritis with crescents and seven patients also had segmental necrosis of the glomerular capillary wall. Most of them also presented with storiform fibrosis and lymphoplasmacytic infiltration in renal interstitium with IgG4 positive plasma cells more than 10/high‐power field. Eight patients achieved remission with improved renal function, the other two patients were on maintenance dialysis. The IgG4 subclass of MPO‐ANCA was higher in the concomitant group than that in AAV alone group. A merge of IgG4 and MPO immunofluorescence was observed in parts of the mesangium of concomitant AAV and IgG4‐RD patients. For complement components, Bb and mannose‐binding lectin were elevated in serum of concomitant AAV and IgG4‐RD patients. Conclusion: We showed a new overlap syndrome of AAV and IgG4‐RD, in which the IgG4 subclass of ANCA may be a pathogenic factor.